Jaccottet and Mahon - Louth, C (Carcanet Press Limited, 2021)
The poetry of Philippe Jaccottet, who died on 24 February at the age of 95, having in 2014 been sealed by the ‘tombstone’, as he felt it to be, of ‘entering into’ the gilt-and-leather Pléiade, is best-known in English in the translations of Derek Mahon. They were published in Penguin International Poets in 1988, the series in which Mahon’s own Selected Poems later appeared, and then a decade later in a smaller selection as Words in the Air (1998). It’s not hard to find affinities between the two poets, as well as other possible reasons which might have attracted Mahon to Jaccottet, however different they also are. In any case, it’s a notable and in the end quite rare example of a major poet providing extended versions of a major contemporary without working with someone else or from existing translations. In his introduction to the Penguin Mahon calls Jaccottet a ‘secular mystic’ and those words have since been used of Mahon himself by various critics too. Both poets evoke Paul Éluard’s idea that another reality exists, but within rather than beyond the world we know. Jaccottet’s word for this ‘other reality’ is ‘l’illimité’, that which has no limits, and he suggests that beauty arises when ‘the limit and that which has no limits become visible at the same time’. Manifestations of such coincidence he looks for above all in the light, in what Mahon calls ‘light-readings’, and says that poems can be thought of as ‘little lamps where the reflection of another light is still ...